Process Oriented Guided Inquiry Learning (POGIL) A Learning Model to Developing Basic Science Process Skills in Madrasah Ibtidaiyah - Khotimah, Husnul; Saefuddin, Asis; Marthyane Pratiwi, Inne (Jurusan Pendidikan Guru Madrasah Ibtidaiyah, 2025)
The research was driven the lack of student engagement in Natural and Social Sciences subjects, particularly in the areas of communication and clasification, both of which are key components of basic science process skills. This research aims to see the improvement of basic science process skills by applying the POGIL learning model in the subjects of Natural Sciences and Social Sciences in each cycle. Conducted through Classroom Action Research using the Kemmis and Taggart model (planning, acting, observing, and reflecting), the study involved 33 fifth-grade students at MIN 1 Bandung City. Data were collected through observations, performance tests, and descriptive tests. Initial findings showed that students’ basic science process skills were at a